Acute leukoencephalopathy associated with daratumumab treatment in POEMS syndrome: a case report - Steinegger, Lukas; Nierobisch, Nathalie; De Vere-Tyndall, Anthony; Schreiner, Bettina; Roth, Patrick; Kappos, Ludwig; Kana, Veronika; Herwerth, Marina (Frontiers in Immunology, 2024)
Daratumumab, a monoclonal antibody against CD38, is increasingly used in the treatment of multiple myeloma, other hematological malignancies and autoimmune diseases. Little is known about its CNS toxicity. We present a case of a patient with POEMS syndrome (syndrome of polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy and skin changes) who developed an acute leukoencephalopathy shortly after initiation of therapy with daratumumab.The patient presented with symptoms of headache and diffuse worsening of a pre-existing tetraparesis. MRI showed a rapidly progressive leukoencephalopathy. Extensive diagnostic evaluation revealed no specific cause, suggesting the leukoencephalopathy to be caused by daratumumab.Our report highlights a probably rare, but clinically significant adverse effect of daratumumab and underlines the necessity of raised vigilance for neurological side effects in patients treated with daratumumab.